Education From The Perspective Of Islamic And Western Scientists (Case Study: Ghazali And Plato) - Orak, Jahanbakhsh (The Turkish Online Journal of Design Art and Communication, 2016)
Philosophy of education deals with study and processes of the aims and nature of the programs and the results of education. Although education and cultivation are two different terms and have two different concepts, they are inseparable in practice. In this study, education was studied from view of two scientists, Ghazali and Plato. Ghazali viewed childhood as being very important and believed that this period should be used as opportunities to teach because what child learns at this time much influence his future. By scientific illumination and as a great coach of Islamic training, Ghazali caused great change through the religious orientation in education and establishing principles, goals and educational methods. One of the great philosophers is Plato, the father of the philosophy of the West. The results indicated that Plato considered educational objectives to include physical goals, talentrelated goals as well as moral, intellectual and social goals. Platonic curriculum include habituating children to play, physical education, teaching reading and writing, training, and teaching philosophy and dialectics and literature. According to Plato, the best teaching method is one that focuses on conversation.
Keywords: education; Islam; the West; Ghazali; Plato; divine development; eğitim; İslam; Batı; Gazali; Platon; ilahi gelişme